2020
DOI: 10.1155/2020/3949735
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness and Safety of Trabeculectomy along with Amniotic Membrane Transplantation on Glaucoma: A Systematic Review

Abstract: Purpose. To determine the effectiveness and safety of trabeculectomy along with amniotic membrane transplantation (AMT) for glaucoma. Methods. This systematic review was performed using RevMan 5.3. We searched PubMed, EMBASE, and the Cochrane Library and included studies published until September 2019. The treatment group included patients with AMT and trabeculectomy (group A), and the control group had only trabeculectomy (group B). We only included randomized controlled trials. The outcomes were intraocular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 39 publications
2
7
0
Order By: Relevance
“…These results are consistent with the results of earlier studies which reported that concomitant AMT under the scleral flap and/or over the sclera, with or without MMC, improved the surgical outcome of trabeculectomy [ 22 , 23 , 25 – 27 , 41 , 42 ]. A randomized trial found that the IOP-lowering effect of AMT-assisted trabeculectomy without MMC was comparable to trabeculectomy with MMC over 2 years and suggested the amniotic membrane as a potential alternative [ 43 ].…”
Section: Discussionsupporting
confidence: 92%
“…These results are consistent with the results of earlier studies which reported that concomitant AMT under the scleral flap and/or over the sclera, with or without MMC, improved the surgical outcome of trabeculectomy [ 22 , 23 , 25 – 27 , 41 , 42 ]. A randomized trial found that the IOP-lowering effect of AMT-assisted trabeculectomy without MMC was comparable to trabeculectomy with MMC over 2 years and suggested the amniotic membrane as a potential alternative [ 43 ].…”
Section: Discussionsupporting
confidence: 92%
“…Some studies report the placement of the AM below of scleral flap in a 'inlay-graft' fashion [48,49], however, other studies state that the tissue is placed over the wound in an 'onlay-graft' fashion to over the entire exposed scleral bed [32,44,50]. As a whole, data shows the application of AM epithelial-side-down [2] when placed onto the wound. Although these differences are present, no obvious differences have been noted regarding outcomes dependent on surgical technique.…”
Section: In Conjunction With Trabeculectomymentioning
confidence: 99%
“…Following this, Shen et al [2] ran a meta-analysis of randomised controlled clinical trials that assess the AM assisted trabeculectomy to trabeculectomy alone. Shen et al's meta-analysis included 174 eyes across 5 studies, the data noted that there was a statistically significant benefit in the intraocular pressure of patients in the AM treatment group at 3 months ( p < 0.0003 ) and 12 months ( p = 0.02 ).…”
Section: In Conjunction With Trabeculectomymentioning
confidence: 99%
See 2 more Smart Citations